Bidirectional Relationship Between Cancer and Heart Failure: Old and New Issues in Cardio-oncology - Edoardo Bertero; Pietro Ameri; Christoph Maack (Cardiac Failure Review)
The main focus of cardio-oncology has been the prevention and treatment of the cardiac toxicity of chemotherapy and radiotherapy. Furthermore, several targeted therapies have been associated with unexpected cardiotoxic side-effects. Recently, epidemiological studies reported a higher incidence of cancer in patients with heart failure (HF) compared with individuals without HF. On this basis, it has been proposed that HF might represent an oncogenic condition. This hypothesis is supported by preclinical studies demonstrating that hyperactivation of the sympathetic nervous system and renin–angiotensin–aldosterone system, which is a hallmark of HF, promotes cancer growth and dissemination. Another intriguing possibility is that the co-occurrence of HF and cancer is promoted by a common pathological milieu characterised by a state of chronic low-grade inflammation, which predisposes to both diseases. In this review, we provide an overview of the mechanisms underlying the bidirectional relationship between HF and cancer.